Disaster resilient built environment: role of lifelong learning and the implications for higher education - Siriwardena, Mohan; Malalgoda, Chamindi; Thayaparan, Menaha; Amaratunga, Dilanthi; Keraminiyage, Kaushal (International Journal of Strategic Property Management, 2013)
Disasters cause considerable damage around the world every year. The built environment is significantly affected by disasters. Whilst the built environment is expected to withstand such occurrences, the construction industry is expected to play a pivotal role in reconstruction of damaged property and infrastructure. Such responses call for technological and managerial innovation. Therefore it is important that construction professionals receive continuous skill development to respond to disaster situations in order to build a disaster resilient built environment. Due to the complexities involved in and due to peculiar nature of disaster situations, lifelong learning is considered as an appropriate way of ensuring continuous education to the various stakeholders of disaster management. The paper reports preliminary findings from a European Commission funded research project aimed at modernising the higher education institutes to support lifelong learning in the built environment. The paper reports the key findings from the literature review and case study on disaster management, emphasising the role of lifelong learning in disaster management education. Empirical data collected as part of the workshop suggest that providing disaster management education as a degree programme is ineffective due to the complexity and multi-disciplinary nature of the subject. Further, the lack of involvement with the industry and the lack of research and development activities on disaster management by built environment professionals act as hindrance to effective disaster management education. In addressing the shortcomings on the existing approaches of disaster management education, this paper concludes that lifelong learning as the most appropriate approach to educate built environment professional in the context of disaster management. First Publish Online: 27 Jun 2013